METHODS OF VISCERAL OBESITY ASSESSMENT IN CLINICAL PRACTICE - G. A. Chumakova; N. G. Veselovskaya (Российский кардиологический журнал, 2016)
Obesity, especially visceral, is a chronic disorder with high risk of cardiometabolic complications. Precise diagnostics of visceral obesity (VO) is not easy, as most methods have benefits and restrictions for application as well. The article focuses on the opportunities and shortcomings of anthropometric, ultrasound methods, and magnet-resonance and computed tomography. We recommend to have broader application of simple and very much available method of direct VO diagnostics — echocardiography — by the measurement of epicardial fat layer.